Android-based Mobile Application for Door-to-Door Product Delivery - Atawneh, Samer; Al-Kasasbeh, Basil; Ben Rshed, Mohammed (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Many companies, such as Aramex, FedEx, and SMSA, offer product delivery services. However, the delivery process through these companies is costly and/or requires the customer’s physical attendance at the company to get the sent shipments. There is a persistent need to improve the delivery process in Saudi Arabia to reduce the effort, cost, and time that the customer spends to get the shipped products. This paper presents a new delivery approach in Saudi Arabia by developing an Android-based MobApp that allows the customers to use their mobile devices to send and receive shipped products at their doorstep by submitting online requests through the developed MobApp. The proposed MobApp, named as Door-to-Door (D2D) product delivery MobApp, guarantees fast and costless service among its competitors. The MobApp will provide its customers a reliable delivery process. It aims to provide a domestic delivery chain with whomever to wherever within Saudi Arabia. In addition, the proposed delivery MobApp allows the customers to create, update and track the delivery orders. Moreover, the proposed D2D delivery MobApp is easy to install and use, it provides a friendly GUI and has a powerful steady performance.